Analysis of Factors Affecting the Human Development Index Between Districts / Cities in North Sumatra Province - Harahap, Misna Doharni; Lubis, Irsad (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2025)
This study aims to determine the effect of the APBD between districts / cities of North Sumatra Province on education levels and health levels. The type of research used is with a quantitative descriptive approach. The data used is secondary data with the period 2017-2021. Data analysis using the BLUE (Best Linear Unbiased Estimator) approach using the Eviews 12 analytical tool. The results showed that the APBD had a positive effect on the level of education and the level of health in 2017-2021.